2007
DOI: 10.1016/j.compbiomed.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mammographic masses using a gradient-based segmentation algorithm and a neural classifier

Abstract: Computerized methods have recently shown a great potential in providing radiologists with a second opinion about the visual diagnosis of the malignancy of mammographic masses. The computer-aided diagnosis (CAD) system we developed for the mass characterization is mainly based on a segmentation algorithm and on the neural classification of several features computed on the segmented mass. Mass-segmentation plays a key role in most computerized systems. Our technique is a gradient-based one, showing the main char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 33 publications
0
31
0
2
Order By: Relevance
“…With the hope of helping radiologists in improving the diagnostic accuracy by providing useful information, computerized analysis of breast lesions on mammograms has been studied by many investigators [9][10][11][12][13][14][15][16][17]. The results of observer performance studies indicated the potential usefulness of the presentation of the likelihood of malignancy of lesions in radiologists' classification of benign and malignant masses [18,19] and clustered microcalcifications [20].…”
Section: Introductionmentioning
confidence: 99%
“…With the hope of helping radiologists in improving the diagnostic accuracy by providing useful information, computerized analysis of breast lesions on mammograms has been studied by many investigators [9][10][11][12][13][14][15][16][17]. The results of observer performance studies indicated the potential usefulness of the presentation of the likelihood of malignancy of lesions in radiologists' classification of benign and malignant masses [18,19] and clustered microcalcifications [20].…”
Section: Introductionmentioning
confidence: 99%
“…We will also show how the IA can be efficient to differentiate malignant mass from benign ones. On the other hand, the RDM descriptor (Alvarenga et al, 2006) (Delogu et al, 2008) was taken a great importance in medical imaging litterature. It is based on the computation of the distances between contour points and gravity center of the region.…”
Section: Context Of State Of the Artmentioning
confidence: 99%
“…The features can be calculated from the mass region contain such as the density, texture, morphologic, shape, and size [5,6,10,11]. Besides, several methods using multiresolution analysis have been proposed for feature extraction in mammograms [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…The classifier is a tool that provides as output the risk degree related to the tissue. Classifiers like support vector machine (SVM) [5,6,12,13], decision tree [5], neural network [5,11], and linear discriminant analysis (LDA) [5,14] have been widely used and performed well. Wu et al [6] segmented the breast tumor by level set method, and the auto-covariance texture features and morphologic features were extracted, then they used the genetic algorithm to detect the significant features and identified the tumors by SVM, which get the accuracy of 95.24 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation